Metabolic Dysfunction Associated Steatotic Liver Disease (MASLD) and Echoparameters of Left Ventricular (LV) Diastolic Dysfunction in Pakistani Population - Zahra, Mehreen; Raza, Muhammad Ali (Indus Journal of Bioscience Research, 2025)
Background: Metabolic dysfunction-associated steatotic liver disease (MASLD) is widely recognized as a risk factor for cardiovascular disease, however its relationship with left ventricular (LV) diastolic dysfunction remains underexplored. Objective: To assess the association between MASLD and echocardiographic parameters of LV diastolic dysfunction in the Pakistani population. Methodology: This case-control research was performed in the Department of General Medicine, Mayo Hospital, Lahore, for a duration of six months (from July 06, 2024 to January 05, 2025). Seventy individuals (35 MASLD patients and 35 controls) were recruited by non-probability sequential sampling. MASLD was identified using ultrasonography, while LV diastolic dysfunction was evaluated using echocardiographic metrics, including LAVI, E/e′ ratio, deceleration time, and isovolumetric relaxation time. Clinical and biochemical characteristics of significance were documented. Data were evaluated using SPSS version 25, with statistical significance established at p < 0.05. Results: In comparison to controls, MASLD patients had significantly higher LAVI (36.2 ± 5.4 mL/m² vs. 29.1 ± 4.8 mL/m², p<0.001), prolonged DT (230.5 ± 24.3 ms vs. 198.2 ± 20.1 ms, p<0.001), and an increased E/e′ ratio (10.6 ± 2.1 vs. 8.2 ± 1.7, p<0.001). Even after controlling for confounders, MASLD continued to be an independent predictor of LV diastolic dysfunction (OR: 3.85, 95% CI: 2.21–6.71, p<0.001). Conclusion: MASLD is significantly associated with LV diastolic dysfunction, emphasizing the need for cardiovascular risk assessment in these patients.